Effects of project-based research work on the career paths of young academics. (1st December 2016) - ,; ,; ,
Abstract : This article focuses on the career chances and working conditions of early-stage researchers as an important category of knowledge workers within the academic system in Germany. We analyse the consequences of a crucial element of this system: the trend to work on externally-funded short-term research projects. Temporary employment in projects opens up opportunities for self-fulfilment and self-organisation, but also increases the risk of self-exploitation. There are, however, variations in the advantages and disadvantages depending on disciplinary structures. Moreover, in order to succeed in science the availability of a variety of capitals is necessary. As a consequence, projectification disadvantages social groups with scarce resources.